Declining Rates of Hip Fracture in End‐Stage Renal Disease: Analysis From the 2003–2011 Nationwide Inpatient Sample. (11th September 2017) - Kim, Sun Moon; Liu, Sai; Long, Jin; Montez‐Rath, Maria E; Leonard, Mary B; Chertow, Glenn M
ABSTRACT: The incidence of hip fracture in patients with end‐stage renal disease (ESRD) is considerably higher than that in the general age‐ and sex‐matched population. Although medical therapy for chronic kidney disease mineral bone disorder (CKD‐MBD) has changed considerably over the last decade, rates of hip fracture in the entire ESRD population have not been well‐characterized. Herein, we evaluated temporal trends in rates of hip fracture, in‐hospital mortality, and costs of associated hospital stay in ESRD. We identified hospitalizations for hip fracture from 2003 to 2011 using the Nationwide Inpatient Sample, a representative national database inclusive of all ages and payers. We incorporated data from the United States Renal Data System and the US Census to calculate population‐specific rates. Between 2003 and 2011, we identified 47, 510 hip fractures in the ESRD population. The overall rate of hip fracture was 10.04/1000 person‐years. The rate was 3.73/1000 person‐years in patients aged less than 65 years, and 20.97/1000 person‐years in patients aged 65 or older. Age‐ and sex‐standardized rates decreased by 12.6% from 2003 (10.23/1000 person‐years; 95% confidence interval [CI], 7.99/1000 to 12.47/1000) to 2011 (8.94/1000 person‐years; 95% CI, 7.12/1000 to 10.75/1000). Hip fracture rates over time were virtually identical in patients aged less than 65 years; however, rates decreased by 15.3% among patients aged 65 years or older; rates declined more rapidly in older women compared with older men ( p for interaction = 0.047). In‐hospital mortality rate after hip fracture operation declined by 26.7% from 2003 (8.6%; 95% CI, 6.8 to 10.4) to 2011 (6.3%; 95% CI, 4.9 to 7.7). In ESRD, age‐ and sex‐standardized hip fracture rates and associated in‐hospital mortality have declined substantially over the last decade. © 2017 American Society for Bone and Mineral Research.